Endoscopic ultrasound in diagnosis of solid pancreatic lesions: Elastography or contrast-enhanced harmonic alone versus the combination - Chantarojanasiri, Tanyaporn; Hirooka, Yoshiki; Kawashima, Hiroki; Ohno, Eizaburo; Kuwahara, Takamichi; Yamamura, Takeshi; Funasaka, Kohei; Nakamura, Masanao; Miyahara, Ryoji; Ishigami, Masatoshi; Watanabe, Osamu; Hashimoto, Senju; Hirakawa, Akihiro; Ratanachu-ek, Thawee; Goto, Hidemi (Endoscopy International Open, 2017)
Background and study aims Endoscopic ultrasound (EUS) elastography (EUS-E) and contrast-enhanced harmonic EUS (CH-EUS) are useful methods for the diagnosis of pancreatic lesions. This study aims to compare the accuracy of combined EUS-E and CH-EUS with that of EUS-E or CH-EUS alone in the differential diagnosis of pancreatic solid lesions. Patients and methods One hundred thirty-six patients with solid pancreatic lesions underwent EUS with both EUS-E and CH-EUS were included. Diagnoses were classified as adenocarcinoma, neuroendocrine tumor (NET), and inflammatory pseudotumor in 95, 22, and 19 patients, respectively. EUS records in each case were rearranged into 3 groups: EUS-E, CH-EUS, and combination. Each modality was randomly reviewed by 3 reviewers with different levels of clinical experience. Sensitivity, specificity, and accuracy of each modality according to each diagnosis group were evaluated. For the combined diagnosis populations, the proportions of correct diagnoses among the 3 modalities were compared by using the multivariate logistic regression analysis.Results The accuracies of EUS-E, CH-EUS, and the combination of them were 68.4 %, 65.4 %, and 75.7 %, respectively, for adenocarcinoma group; 83.8 %, 82.4 %, and 86.8 % for NET group; 80.1 %, 78.7 %, and 81.6 % for inflammatory pseudotumor group. The multivariate logistic regression analysis for the combined diagnosis populations showed that the proportion of correct diagnoses when EUS-E and CH-EUS were combined was slightly higher than with the other 2 modalities, although the significant differences among them were not observed.Conclusion EUS-E and CH-EUS combined may improve differential diagnosis of solid pancreatic lesions compared with use of the individual modalities.